Potencial de demanda energética cero en envolventes industriales: El caso de la vinificación en zonas de gran amplitud térmica. - Ramos-Sanz, Alba Inés (Universidad del Bío-Bío, Chile, 2017)
In this study, a mathematical model was developed for the real-time simulation of a winemaking envelope representative of the national vinification technology of reinforced concrete. Thermal monitoring of the wine stored inside this envelope and another of stainless steel was carried out using HOBO U-12 temperature sensors. The simulation studied the effect on the thermal stability of the wine and the thermal demand originating in the forced convection caused by breezes, under various cellar configurations. With the validated tool, a simple passive optimization was performed on the representative case. Finally, comparing the results of the optimized, simulated cases and the real cases, it was concluded that the representative case has a higher thermo-energy efficiency compared to the stainless-steel cases. Likewise, it was observed that the thermal stability of the wine with zero demand is feasible through the use of envelopes that are suitable for the climate analyzed; with simple optimization measures, this stability comes close to the zero-demand prototype sought after in reference models for energy management.